JOHN DONNEʼS “THE ANNIVERSARIES” AS PETRARCHAN TEXTS - Mariana V. Markova. (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The purpose of the article is to examine John Donneʼs poems “An Anatomy of the World: The First Anniversary” and “Of the Progress of the Soul: The Second Anniversary” as a part of the Petrarchan poetic tradition. In order to accomplish this purpose, we have applied a complex approach by using elements of biographical, genealogical, typological, hermeneutic, comparative and structural-semiotic methods of literary analysis. The article analyzes scientific investigations devoted to the issue of the Petrarchan impulses in “The First” and “The Second Anniversary”. The circumstances and history of their creation have been disclosed, their dominant problems have been highlighted, and their direct connection with the poetic practice of European Petrarchism has been emphasized. It has been noted that the initial idea of the writer – to connect the decay and decline of the world with the death of an innocent young girl – was not new. He often used the theme of death and in such poems as, for example, “A Fever” and “A Nocturnal upon Saint Lucyʼs Day”, the death of the heroine was associated with catastrophic, sometimes even global consequences for the natural world and society. And this is not surprising, because at the center of John Donneʼs universe and the microcosm of his lyrical hero, there has always been a woman – the basis and determinant of all processes and phenomena. Naturally, with her death, the world loses its foothold and all possibilities for further existence and development. Such a position absolutely correlates with the European Petrarchistsʼ concept of a woman, where the death of the main character was traditionally accompanied by hyperbolized cries, titanic suffering and signs of cosmic disturbance. Conclusion. Based on the direct textual parallels between “Canzoniere” and John Donneʼs poems we present the following research results. In “The Anniversaries” the English author involved almost the entire arsenal of images (the main character as a queen, the soul of the universe, its heart and beauty, foundation, measure and harmony, etc.), motifs (the rapid decline and complete destruction of the world due to the tragic death of the heroine; the ennobling influence that Elizabeth had on everything surrounding her; poetic creativity, which may be immortal, but is unable to reflect the external and internal perfection of the girl; the importance of neglecting the earthly for the sake of the heavenly, for what the short life of the heroine can serve as an example; a woman as the cause of a manʼs death; the unearthly, angelic nature of the main character, who had no place on the sinful earth, etc.), means and methods of images creation (portrayal of a female character using images of gold and various kinds of jewelry; excessive idealization of the heroine; excessive hyperbolization and affectation; complex rhetorical periods, etc.), which in Francesco Petrarchʼs “Canzoniere” dealt with the untimely death of Laura, its irreparable consequences and the protagonistʼs suffering on this occasion. At the same time, John Donne significantly expanded the semantic volume of the borrowed Petrarchan elements, and even those which were only barely outlined in the works of the Italian poet himself, acquired additional details (for example, the comparison of Elizabeth with the state) and scale (pictures of the soul’s afterlife journey through the heavenly spheres) in the English writerʼs texts. It has been shown that many of the Petrarchan images are even more hyperbolic in John Donneʼs poems (grave world, corpse world). At the same time, it has been established that certain images and motifs are also somewhat simplified, schematized (the heroine’s singing in the heavenly choir). Therefore, it has been concluded that, when turning to “Canzoniere” as a source of the toposes and concepts, the writer did not just use them as a convenient but frozen language strategy, which was typical for most European Petrarchists, but creatively reinterpreted them according to his own intentions. It has been proved that reading John Donneʼs “The First” and “The Second Anniversary” through the prism of Petrarchan receptions not only allows us to put these texts into a very organic analytical context, but also helps to solve certain applied problems, such as, for example, the problem of the prototype of the main character.